Seleção de pessoal: considerações preliminares sobre a perspectiva behaviorista radical - SANTOS, José Guilherme Wady (2013)
The goal of the Personnel Selection process is to identify the applicant that best meets the requirements for a specific job. The common practice of classifying job applicants, by personal characteristics considered necessary for successful performance at a specific job position, typically emphasizes internal, rather than environmental, causes of behavior. The current article discusses some aspects related to the difficulty of implementing selection processes based on a radical behaviorist approach and also criticizes the use of psychological tests and categories in the process of personnel selection. It also suggests the need for of clear and objective definitions of behaviors and skills that are relevant for each job position, as well as the identification of the necessary conditions for the occurrence of these behaviors and skills. The need for a behaviorist model of personnel selection is thus suggested. Such a model would include techniques that allow for the observation of the relevant behaviors in analog situations, functional analyses, and possibly, minimal training of some of the required skills, before the final decision is made.